The Moderating Roles of Resilience and Coping Strategy on Well-Being of Victimized Forensic Workers - Rou, Caroline (International journal of offender therapy and comparative criminology, 2025)
Previous research on workplace victimization has often disregarded forensic psychiatric populations and not yet been extended to the coronavirus pandemic. The present study expected the isolation of the government-issued lockdown to increase aggressive behavior in forensic patients, ultimately decreasing the general well-being of victimized forensic workers. Possible buffering protective factors (resilience and active coping) and enhancing risk factors (avoidant coping and passive coping) were investigated with the intention of optimizing the general well-being of at-risk forensic workers. The valid sample (N = 311) consisted of Dutch and Belgian forensic workers (74.6% females) with at least 9 hours of weekly patient contact, and with a mean age of 37.99 (SD = 12.20). Participants reported the number of violent incidents in the past 2 months, as well as completed a questionnaire battery including measures of well-being, resilience, and coping strategies. A significant increase of victimization during the lockdown compared to after it was lifted was found, however, the study did not find evidence to support that this negatively influenced the worker’s general well-being. Active coping was found to be a significant moderator and protective factor for the general well-being of victimized forensic workers. In contrast, resilience, avoidant and passive coping were not significant moderators in this association. The present study has valuable clinical implications that could lead to preparatory and preventative measures for forensic workers at risk of being victimized. Future research may investigate constructs such as life satisfaction and post-traumatic growth, as well as be broadened into prison populations.